2018
DOI: 10.1002/2017wr021102
|View full text |Cite
|
Sign up to set email alerts
|

Trade Openness and Domestic Water Use

Abstract: We contribute to the debate over globalization and the environment by asking, what is the impact of trade on national water use? To address this question, we employ econometric methods to quantify the causal relationship between trade openness and water use. Specifically, we use the instrumental variables methodology to evaluate the impact of trade openness on domestic water withdrawals in agriculture and industry. We find that trade openness does not have a significant impact on total or industrial water with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 25 publications
1
47
0
Order By: Relevance
“…Common endogeneity problems (dashed arrows) include (i) omitted variables (e.g., wealth affects both water use and trade openness) and (ii) reverse causality (e.g., water use can increase trade openness by empowering agricultural lobbies). Dang and Konar () address these concerns by using geographic determinants of trade (e.g., distance) as instrumental variables (iii). (b) Difference‐in‐differences is used to estimate the effect of the 2013 refugee crisis on irrigated land area in Southern Syria using Northern Jordan as a control group (Müller, Yoon, et al, ); error bars indicate standard deviations across years.…”
Section: Problem 1: Empirical Causal Inferencementioning
confidence: 99%
See 3 more Smart Citations
“…Common endogeneity problems (dashed arrows) include (i) omitted variables (e.g., wealth affects both water use and trade openness) and (ii) reverse causality (e.g., water use can increase trade openness by empowering agricultural lobbies). Dang and Konar () address these concerns by using geographic determinants of trade (e.g., distance) as instrumental variables (iii). (b) Difference‐in‐differences is used to estimate the effect of the 2013 refugee crisis on irrigated land area in Southern Syria using Northern Jordan as a control group (Müller, Yoon, et al, ); error bars indicate standard deviations across years.…”
Section: Problem 1: Empirical Causal Inferencementioning
confidence: 99%
“…Dang and Konar () used this approach to address endogeneity in the example discussed in section , when estimating the effect of a country's openness to international trade on domestic water withdrawals for agriculture. The Dang and Konar () study is an example of a quasi‐experimental approach that compares countries across levels of trade openness (i.e., “comparison groups” are levels of trade openness).…”
Section: Problem 1: Empirical Causal Inferencementioning
confidence: 99%
See 2 more Smart Citations
“…For an overview of the debate surrounding VWT please see Antonelli and Sartori (2014). However, recent work, using advanced econometric methods, has demonstrated that trade does, on average, lead nations to use less water in agriculture (Dang & Konar, 2018). It is important to note that water is only one of a suite of factors of production in agriculture (Kumar & Singh, 2005).…”
Section: 1029/2018wr024292mentioning
confidence: 99%